Domestic courts as guarantors of international climate cooperation: insights from the German Constitutional Court’s Climate Decision - Jahn, Jannika (MPIL research paper series, 2022)
Domestic courts in various countries have begun to scrutinize the political branches’ responses to climate change. A central argument against court interventions pushing individual state’s climate actions is that the individual state cannot effectively promote climate protection and instead, will suffer economic disadvantages in global competition. The article counters this criticism with the thesis that judicial interventions contribute to an effective realization of climate protection if they strengthen international cooperation. To substantiate the thesis, the article draws on the economic analysis of law to examine states’ decision-making rationalities for entering international agreements. It then analyzes how judicial interventions may influence these parameters, with a particular focus on the recent climate decision of the German Constitutional Court and embeds the domestic court decisions in an emerging public relations law that closely interlinks constitutional and international climate law.
Gesehen am 20.08.2022
Forthcoming in: International Journal of Constitutional Law